ANALISIS YURIDIS DEGRADASI KEKUATAN PEMBUKTIAN DAN PEMBATALAN AKTA NOTARIS MENURUT PASAL 84 UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS - Idris Aly Fahmi (Arena Hukum, 2013)
Abstract The objectives of this journal are to describe and to analyze the boundary of the degraded verifying strength and the boundary of the cancellation of Notary Public Certificate based on Article 84 Act No.30 of 2004 about The Rank of Notary Public, and also to describe and to analyze the mechanism of the application of civil sanction against Notary Public in the case of the degraded verifying strength and the cancellation of Notary Public Certificate. Method used in this journal is normative juridical with statute and conceptual approaches. Result of research indicates that the boundary of Notary Public Certificate with degraded verifying strength into a merely under-hand document is when Notary Public Certificate has violated Article 16 Verse (1) Letter l, Article 16 Verse (7), Article 16 Verse (8), Article 41 with reference to Article 39 and 40, and Article 52 of Act No. 30 of 2004 about The Rank of Notary Public. The boundary of the cancellation, or being cancelled based on law, pursuant to Article 84 of Act No.30 of 2004 about The Rank of Notary Public, is when Notary Public Certificate deviates from what has been stated in Article 16 Verse (1) Letter i, Article 16 Verse (1) Letter k, Article 44, Article 48, Article 50, and Article 51 of Act No.30 of 2004 about The Rank of Notary Public. The mechanism of the application of civil sanction against Notary Public is decided through the court process begun with the allegation by the parties in the certificate who is adversely affected due to the mistake or the negligence of Notary Public which is considered as violating Article 84 of Act No.30 of 2004 about The Rank of Notary Public, and/or contravening against the provision of Article 1865 of Civil Code. Key words: degradation, verifying strength, cancellation, notary public certificate AbstrakTujuan dari penulisan jurnal ini adalah untuk mendeskripsikan dan menganalisis batasan degradasi kekuatan pembuktian dan batasan pembatalan akta Notaris menurut ketentuan Pasal 84 Undang-undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris, dan untuk menganalisis mekanisme penerapan sanksi perdata terhadap Notaris dalam hal terjadinya degradasi kekuatan pembuktian atau pembatalan akta Notaris. Metode penelitian yang digunakan dalam penulisan jurnal ini adalah penelitian yuridis normatif dengan pendekatan perundang-undangan, dan pendekatan konseptual. Berdasarkan hasil penelitian, batasan akta Notaris yang terdegradasi kekuatan pembuktiannya menjadi akta di bawah tangan adalah akta Notaris yang melanggar ketentuan Pasal 16 ayat (1) huruf l, Pasal 16 ayat (7), Pasal 16 ayat (8), Pasal 41 dengan menunjuk ketentuan Pasal 39 dan Pasal 40, serta melanggar ketentuan Pasal 52 Undang-undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris. Sementara batasan akta Notaris yang mengalami pembatalan atau batal demi hukum menurut Pasal 84 Undang-undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris adalah melanggar kewajiban sebagaimana disebutkan dalam Pasal 16 ayat (1) huruf i, Pasal 16 ayat (1) huruf k, Pasal 44, Pasal 48, Pasal 50, dan Pasal 51 Undang-undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris. Mekanisme penerapan sanksi perdata terhadap Notaris dijatuhkan melalui proses peradilan yang diawali oleh gugatan para pihak dalam akta yang merasa dirugikan akibat kesalahan atau kelalaian Notaris yang melanggar ketentuan pasal 84 Undang-undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris sebagaimana diatur dalam ketentuan Pasal 1865 KUHPerdata dan sejalan dengan teori pembuktian.Kata kunci : degradasi, kekuatan pembuktian, pembatalan, akta notaris